Analisis Pemanfaatan Platform Merdeka Mengajar Terhadap Pengembangan Kompetensi Pedagogik Guru UPT SDN 14 Turatea Kabupaten Jeneponto - khairunnisa, Nur; Irfan, Muhammad; Rahman, Abdul (PT Ininnawa Paramacitra Edukasi, 2024)
This study aims to explain the utilization of the Merdeka Mengajar Platform (PMM) for the development of pedagogical competencies among teachers at UPT SD Negeri 14 Turatea Jeneponto. This research employs a qualitative method with a descriptive qualitative approach. Data were collected through in-depth interviews with seven respondents, including the school principal and teachers from grades 1 to 6 at UPT SDN 14 Turatea, Kabupaten Jeneponto. Based on the Technology Acceptance Model (TAM), PMM is effective in enhancing teachers' pedagogical competencies. Perceived ease of use indicates that teachers find PMM comfortable to use due to its simple interface, ease of access, adequate technical support, good socialization, and flexible access. Perceived usefulness shows that PMM is not just an administrative tool but also an essential resource with activities like self-training, videos, teaching tools, learning communities, collaboration, and publication of works that support the development of teachers' pedagogical competencies in creating a safe learning environment, effective teaching, and improved assessment and feedback. Attitude towards using reveals that teachers have a positive attitude towards PMM because the activities offered are considered beneficial and of high quality. Behavioral intention to use highlights that the benefits of PMM and its economical cost encourage continuous use. Furthermore, actual system use shows that high accessibility and significant usage duration reflect the dedication of teachers in utilizing PMM to enhance their pedagogical competencies. Keywords: Platform Merdeka Mengajar, Pedagogical Competence, Technology Acceptance Model (TAM), Teacher Development